Media Framing on the Controversy of Puppet Prohibition in Indonesia: A Comparative Study of Republika.co.id and Detik.com - Agustianingsih, Erza; Riyadin saputro, Dedi (Social Sciences and Humanities Reviews, 2025)
Background: The issue of banning puppets by Ustadz Khalid Basallamah in his lecture in early 2022 triggered public controversy and became the main spotlight in various media. Puppets, which have been known as a cultural da'wah media, are suddenly questioned from the perspective of religious law, thus giving rise to a debate between traditional values and Islamic interpretation. Online media such as Republika.co.id and Detik.com are the main channels in framing this issue. Aims: This study aims to analyze how the framing of news is carried out by Republika.co.id and Detik.com on the issue of wayang ban by Ustadz Khalid Basallamah, as well as reveal the difference in perspectives between the two in compiling media narratives Methods: This study uses a descriptive qualitative approach with the Framing analysis model of Zhondang Pan & Gerald M. Konsicki, which includes four text structures: syntactic, scripted, thematic, and rhetorical. Data were obtained from news articles in both media during February 2022 and analyzed based on the textual elements that shape the way the media frames reality. Result: The results of the study show that Republika.co.id frame the issue with a moderate Islamic approach, support local culture-based da'wah, and display a peaceful and harmonious narrative. Instead, Detik.com highlights controversial aspects by featuring public figures' responses and political-legal narratives. These differences show how ideology and reader segmentation affect news framing. Conclusion: The media has an active role in shaping public perception of religious and cultural issues through framing strategies tailored to their identities and interests. Therefore, media literacy is important so that the public can respond to news critically and objectively.